Comparison of outcomes between novel oral anticoagulants and warfarin monotherapy in patients with left atrial appendage closure: A systematic review and meta-analysis - Sun, Bing; Chen, Rui Rui; Gao, Chao; Tao, Ling (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background: Pivotal trials of percutaneous left atrial appendage closure (LAAC) used dedicated post-procedure antithrombotic protocols. However, there is no consensus on the selection of new oral anticoagulants (NOAC) and warfarin monotherapy after LAAC. This study aims to compare NOAC with warfarin monotherapy for efficacy and safety in patients undergoing LAAC. Methods: A database search was conducted using PubMed, EMBASE, Cochrane Library, and Clinicaltrials.gov for trials that compared NOAC with warfarin monotherapy after LAAC. The effective outcomes included any major adverse events (all-cause death, stroke, major bleeding) and their individual components. Safety outcomes included all-cause death, major bleeding, total bleeding, DRT, and PDL>5mm. Results: We included 10 nonrandomized clinical trials with 10337 patients, of whom 4960 patients received NOAC, while 5377 patients received warfarin. There were no statistically significant differences in any major adverse events (LogOR:-0.11,95%CI:-0.27,0.04,P=0.16), stroke (LogOR:0.00,95%CI:-0.42,0.42,P=1.00), all-cause death (LogOR:-0.23,95%CI:-0.48,0.02,P=0.07), major bleeding (LogOR:-0.22,95%CI:-0.45,0.01,P=0.06). NOAC was associated with a significant reduction in total bleeding (LogOR:-1.01,95%CI:-1.47,-0.55, P<0.0001) compared to warfarin. No statistically significant differences were found in DRT (LogOR:-0.19,95%CI:-0.15, 0.52,P=0.27) and PDL>5mm (LogOR:0.19,95%CI:-0.33,0.72,P=0.47). Meta-regression and subgroup analysis showed that total bleeding (LogOR:-1.56,95%CI:-2.15,-0.97, P<0.001) was significantly lower in the NOAC group in the subgroup of <75y. Conclusion: After LAAC, NOAC monotherapy was associated with a lower risk of bleeding compared to warfarin monotherapy for 45 days. There was no significant difference between NOAC and warfarin in terms of other results.